The Effect of Leverage and Liquidity Ratios on Earnings Management and Capital of Banks Listed on the Tehran Stock Exchange - Abdolkarim Moghaddam; Narges Abbaspour (International Review of Management and Marketing, 2017)
Banks, like all profit institutions seek their profitable growth and maximize their shareholders' wealth, increased profitability of the banks on the one hand, increases the company's value and on the other hand, increases executives' compensation and increases their tenure and because the same reason, bank managers have high motivation to increase profits through discretionary accruals. The capital structure also due to the relationship with credit risk and cost of capital is considered as one of important issues in the banks, so, the current research aimed to determine the e of leverage and liquidity ratios on earnings management and capital of banks listed on the Tehran Stock Exchange. In this research, financial information of 14 banks listed on the Tehran Stock Exchange during the period 2010 to 2015 have been studied and for performing this study, multivariate linear regression analysis using panel data has been used. The results show that financial and liquidity leverage has significant positive effect on earnings management of banks, therefore increasing the degree of financial leverage and by increasing bank liquidity, the possibility of using discretionary accruals and earnings management at banks increase. The results also showed that financial leverage has a significant negative effect on the bank's capital adequacy ratio and with increasing financial leverage bank capital adequacy ratio is reduced.